Staphylococcal Surface Display of Metal-Binding Polyhistidyl Peptides - Samuelson, Patrik (American Society for Microbiology, 2000)
Recombinant Staphylococcus xylosus and Staphylococcus carnosus strains were generated with surface-exposed chimeric proteins containing polyhistidyl peptides designed for binding to divalent metal ions. Surface accessibility of the chimeric surface proteins was demonstrated and the chimeric surface proteins were found to be functional in terms of metal binding, since the recombinant staphylococcal cells were shown to have gained Ni(2+)- and Cd(2+)-binding capacity, suggesting that such bacteria could find use in bioremediation of heavy metals. This is, to our knowledge, the first time that recombinant, surface-exposed metal-binding peptides have been expressed on gram-positive bacteria. Potential environmental or biosensor applications for such recombinant staphylococci as biosorbents are discussed.